Manifestation of pathognomonic signs in modeling diabetes mellitus with streptozotocin in BALB/c mice - A. V. Sorokina; A. K. Zhanataev; Z. V. Chayka; I. A. Miroshkina; A. A. Lisitsyn; A. D. Durnev (LLC "Publisher OKI", 2023)
Relevance. Diabetes mellitus is a widespread, socially significant disease. In this regard, it is important to obtain an experimental model that precedes subsequent experiments on pharmacological screening and/or study of the mechanism of action of antidiabetic agents.The aim of this work was a comparative assessment of the manifestation of hyperglycemia, DNA damage, and morphology of internal organs in BALB/c mice in the modeling of diabetes mellitus by a single administration of streptozotocin at a dose of 200 mg/kg and its fractional, five-day administration at a rate of 40 mg/kg per day.Methods. Streptozotocin was used as an inducer of diabetes. The drug was administered to mice once at a dose of 200 mg/kg or 5 times daily at a dose of 40 mg/kg. We monitored hyperglycemia, DNA damage in the cells of the brain, liver, kidneys, pancreas and testes, and also assessed the microscopic picture of individual internal organs, including the pancreas.Results. In both variants of the experiment, the reproduction of pathognomonic signs of diabetes mellitus is traced. They are somewhat more clearly seen in the variant of the experiment with a fractional, five-day administration of streptozotocin in single doses of 40 mg/kg.